The Use of Local Anesthesia in Pediatric Dentistry: A Survey of Specialists' Current Practices in Children and Attitudes in Relation to Articaine - Thikrayat Bani-Hani; Rami Al-Fodeh; Abedelmalek Tabnjh; Rona Leith (Hindawi Limited, 2024)
Aims. This study aimed to evaluate the clinical practices of local anesthesia in children. The study also sought to investigate pediatric dentists' views on articaine infiltration anesthesia and their willingness to use it to replace the inferior dental nerve block in primary molars. Materials and Methods. A cross-sectional survey was emailed to 183 registered specialists. Descriptive statistics along with chi-square and Fisher's exact tests were used for data analysis. Results. A total of 72 responses were received. The sample consisted of 62 (86.1%) females and 10 (13.8%) males with varying levels of experience. The vast majority of respondents (98.6%) used topical anesthesia in their practice with children. The most frequently used anesthetic agent was 2% lidocaine (72.2%) followed by 4% articaine (54.2%). The entire sample indicated that they frequently find difficulties in dose calculation for their child patient. Gender and level of experience did not significantly influence specialists' practice or their knowledge of local anesthesia. More than a third (31.9%) of participants were not happy to replace the block anesthesia with articaine infiltration for the treatment of lower primary molars. The most indicated reasons for this unwillingness were lack of effectiveness (11%) and inadequate scientific evidence (11%). Conclusion. Most pediatric dentists used topical anesthesia with children. Lidocaine was the most commonly used injectable local anesthesia. Specialists' current practices of local anesthesia in children generally conformed well to good standards. However, inadequate knowledge regarding dose calculation was revealed. In addition, specialists' reluctance to use articaine infiltration instead of the block anesthesia was evident in the current population. Further studies, with larger sample size are encouraged.